Kedewasaan Wanita Dalam Pemikiran Hukum Tentang Posisi Wali Dalam Akad Pernikahan (Kajian Al-Fiqh ‘Ala Al-Madhahib Al-Arba’ah) - Hisbulloh Hadziq (MAHAKIM Journal of Islamic Family Law, 2019)
This article studies the opinion of fuqaha on the role of guardians in marriage. Some scholar consider it as an obligation, while others do not argue that it should be in marriage. And what is the relationship between the guardian with the readiness/maturity of the bride candidate.Although the marriage was only performed by both brides, but to start with it, the involvement of others is required, such as guardians. This article is a literal study where data is obtained through the exploration of the classical books in four popular madhhabs.These datas are then analyzed using acomparative approach.The results concluded that the existence of the guardian is closely related to the maturity of the prospective bride to establish a marriage.